Caracterización De Los Consumidores De Ropa De Moda - Wong, Adriana Méndez; Ruiz, Edith Reyes; Siller, Jesús Francisco Mellado; Ramirez, Karina Lizbeth Rodriguez (European Scientific Journal, ESJ, 2018)
This study is a Marketing work about the life style of the consumers related to their fashion clothing purchases. For that an instrument is applied using a scale proposed by Chegedzai, Manillall and Lawrence Mandhalazi (2014) who identified seven constructs for the typology: Fashion Aware, Hedonist, Brand Aware, Innovative, Quality Aware, Undecisive and Brand Loyalty. Its a transversal, quantitative, exploratory and descriptive investigation. The sample shows 1000 individuals from 21 to 80 years old, in Saltillo, Coahuila, Mexico, validating a 4o items instrument acquiring an Alfa de Cronbach of 0.952. The questions were categorical and the answers were indicted on a Likert Scale from 1 to 5. The results on relation to the analyzed dimensions, point that the interviewed attempt to buy quality clothes and aknowledge that it is an effort to achieve it because their incomes are a limiting to their purchase of High End clothing brands. The genre affects on the purchase decision, concluding that there are meaningful differences between men and women: the women enjoy more buying clothes, they have more fun while they’re doing it and dedicate more time to the activity mentioned. It is a Project from the Red Nacional de Investigación “Gestion de la Mercadotecnia” del Consorcio de Universidades Mexicanas. (National Net of Investigation “Marketing management” of the Mexican Universities Consortium).